Impact of Energy Use on Air Pollution: Evidence from OCED Countries - Gara, Atdhetar; Hadzimustafa, Shenaj; Amaxhekaj, Gazmend; Qehaja, Driton (Ekonomika, 2024)
Air pollution poses significant environmental and health risks, with numerous studies suggesting its dire consequences ranging from respiratory diseases to global climate change implications. In this context, understanding energy consumption patterns and their impact on air pollution is critical, especially in developed nations with high energy consumption rates. This paper empirically analyzes the impact of energy use on air pollution in OECD countries – a group of nations that play a pivotal role in global energy consumption and policy-making. Despite their economic advancements, the implications of their energy choices on air quality have not been extensively studied, presenting a gap in the literature. Spanning 12 years from 2010 to 2021, our research encompasses a total of 456 observations, employing panel data. We aim to unveil the relationship between energy use, both traditional and renewable and air pollution levels. The variables studied include Energy use per capita, Alternative and nuclear energy, Greenhouse gas emissions, Energy imports, Access to electricity, and the production of renewable energy (air, water, solar, geothermal). Leveraging various econometric models such as OLS, OLS Robust, fixed, and random effects models, our findings reveal that electricity use exacerbates air pollution levels. Particularly, the increase in carbon dioxide, coupled with the rising access to electricity, deteriorates air quality. In contrast, electricity sourced from renewables like water, wind, nuclear, and geothermal energy aids in mitigating air pollution, emphasizing the importance of sustainable energy choices for future policy considerations in OECD nations.
Keywords: Pollution; Air; Energy